Myofibril and Mitochondrial Area Changes in Type I and II Fibers Following 10 Weeks of Resistance Training in Previously Untrained Men - Ruple, Bradley A.; Godwin, Joshua S.; Mesquita, Paulo H. C.; Osburn, Shelby C.; Sexton, Casey L.; Smith, Morgan A.; Ogletree, Jeremy C.; Goodlett, Michael D.; Edison, Joseph L.; Ferrando, Arny A.; Fruge, Andrew D.; Kavazis, Andreas N.; et al. (Frontiers in Physiology, 2021)
Resistance training increases muscle fiber hypertrophy, but the morphological adaptations that occur within muscle fibers remain largely unresolved. Fifteen males with minimal training experience (24±4 years, 23.9±3.1 kg/m2 body mass index) performed 10 weeks of conventional, full-body resistance training (2x weekly). Body composition, the radiological density of the vastus lateralis muscle using peripheral quantitative computed tomography (pQCT), and vastus lateralis muscle biopsies were obtained one week prior to and 72 hours following the last training bout. The determination of fiber type and the quantification of myofibril and mitochondrial areas in type I and II fibers were performed using immunohistochemistry (IHC) techniques. Relative myosin heavy chain and actin protein abundances per wet muscle weight as well as citrate synthase (CS) activity assays were also obtained on tissue lysates. Training increased whole-body lean mass, mid-thigh muscle cross-sectional area, mean and type II fiber cross sectional areas (fCSA), and maximal strength values for leg press, bench press, and deadlift (p<0.05). The intracellular area occupied by myofibrils in type I or II fibers were not altered with training, suggesting a proportional expansion of myofibrils with fCSA increases. However, our histological analysis was unable to differentiate if increases in myofibril number or girth occurred. Relative myosin heavy chain and actin protein abundances also did not change with training. IHC indicated training increased mitochondrial areas in both fiber types (p=0.018), albeit CS activity levels remained unaltered with training suggesting a disconnect between these assays. Interestingly, although pQCT-derived muscle density increased with training (p=0.036), suggestive of myofibril packing, a positive association existed between training-induced changes in this metric and changes in type I+II myofibril areas (r=0.600, p=0.018). Our data imply that shorter-term resistance training promotes a proportional expansion of the area occupied by myofibrils and a disproportional expansion of the area occupied by mitochondria in type I and II fibers. Additionally, IHC and biochemical techniques should be viewed independently from one another given the lack of agreement between the variables assessed herein. Finally, the pQCT may be a viable tool to non-invasively track morphological changes in muscle tissue.